Osoba i przesłanie św. Franciszka - Roland Prejs (Polonia Sacra)
St. Francis is undoubtedly one of the most popular Christian saints. There are two different biographies of St. Francis. The biography by Thomas da Celano is a historical description of St. Francis` life although written according to the medieval hagiographical canons. St. Bonaventure was a theologian and philosopher first of all. He shows us St. Francis as a perfect follower of Jesus. The other biographies relied heavily on Vita prima, Vita secunda or Legenda maior. Notwithstanding the first biographies based on the very first documents and contemporary relations, some questions still linger. Nevertheless, St. Francis message is clear: equality of all before God, everyone is called for the evangelical life, evangelism through good example rather than through words alone. Important is an emulation the radical poverty of Jesus, fidelity and obedience to the Church, which is represented and guided by pope.